Capacidade reprodutiva de fêmeas de Apanteles galleriae (Hymenoptera, Braconidae) em lagartas de Galleria mellonella e Achroia grisella (Lepidoptera, Pyralidae) criadas com dietas diferentes Reproductive capacity of Apanteles galleriae females (Hymenoptera, Braconidae) in Galleria mellonella and Achroia grisella larvae (Lepidoptera, Pyralidae) reared on different diets - Giuliano Grici Zacarin; Nivar Gobbi; José Chaud-Netto (Iheringia: Série Zoologia, 2004)
The reproductive capacity of females of Apanteles galleriae (Wilkinson, 1932) was evaluated in fifth instar caterpillars of Galleria mellonella (Linnaeus, 1758) and Achroia grisella (Fabricius, 1754) fed on standard diet and diets enriched with protein. The reproductive capacity of parasitoid females on fifth instar caterpillars of G. mellonella and A. grisella with variable weight was also evaluated. The host weight interfered in the sex ratio of the obtained parasitoids. In heavier caterpillars, the investment in female descendants was greater than in males, and in lighter caterpillars the inverse occurred.